Patterns of change in subjective cognitive complaints are associated with cognitive decline and dementia risk: Findings from the Sydney Memory and Ageing Study: Neuropsychology: Awareness of cognitive capacities and subjective cognitive decline. (7th December 2020) - Numbers, Katya T.; Lam, Ben C.P.; Crawford, John D.; Kochan, Nicole A.; Sachdev, Perminder S.; Brodaty, Henry
Abstract: Background: Subjective cognitive complaints (SCCs) are now an established risk factor for dementia, however, little is known about whether changing patterns in SCCs over time are associated with cognitive decline and dementia risk. We examine the trajectory of SCCs over a 6‐year period to determine whether intraindividual patterns of reporting SCCs over time is related to cognitive decline and incident dementia. Method: Participants were 1037 older adults without dementia ( M age = 78.65 years; 55% females) from the Sydney Memory and Ageing Study who were followed‐up biennially. Global cognition was measured using a comprehensive neuropsychological battery, and clinical diagnoses were made by an expert consensus panel. SCCs were obtained as participants' response to a single question concerning their subjective report of memory decline. Patterns of SCCs over time were modelled by conducting categorical latent growth curve analysis using the logit transformation (Figure 1). We examined the associations between average level of SCC likelihood and change in SCC likelihood, with global cognition over six years using latent growth curve analysis, and with risk of incident dementia over 10 years using Cox regression. Result: In this community‐dwelling older adult sample, there was an annual 10% increase in the odds of reporting SCCs (Figure 2). After controlling for demographics, depression, and personality, results revealed a negative longitudinal association between the slope of SCCs and the slope of global cognition scores, such that participants with an increasing propensity of reporting SCCs over time also showed a steeper rate of decline in global cognition (Figure 4). Cox regression revealed an association between increased SCCs and incident dementia risk (Table 1). That is, participants with an increasing propensity of reporting SCCs over time are also at greater risk for developing dementia (Figure 5). Conclusion: This is the first study to use latent growth curve analysis to examine patterns of change in SCCs overtime. Traditionally, studies examining SCCs longitudinally categorise people as 'stable' versus 'not stable', however, important information may be lost this way. Understanding patterns of change in SCC reporting over time has significant potential to identify individuals at greater risk of cognitive decline and incident dementia.